Steel connection analysis - Rugarli, Paolo, 1963- (John Wiley & Sons, Inc., 2018)
First book to discuss the analysis of structural steel connections by Finite Element Analysis--which provides fast, efficient, and flexible checking of these vital structural components.
Keywords: Steel, Structural -- Testing.; Finite element method.; Building, Iron and steel -- Joints.; elektronické knihy; electronic books